2014
DOI: 10.1530/rep-13-0426
|View full text |Cite
|
Sign up to set email alerts
|

Food restriction during lactation suppresses Kiss1 mRNA expression and kisspeptin-stimulated LH release in rats

Abstract: Among the numerous physiological changes that accompany lactation is the suppression of the reproductive axis. The aim of this study was to investigate a possible role for the kisspeptin system in the restoration of the hypothalamic-pituitary-gonadal axis during late lactation in rats using a food restriction model that allows manipulation of the duration of lactational anovulation. Kiss1 mRNA expression and kisspeptin-immunoreactive cell counts were examined in both food-restricted dams and ad libitum (AL)-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…The present data showing only partial reversal of the lactation‐induced suppression of kisspeptin expression in the RP3V of mice by bromocriptine are strikingly similar to that recently reported in rats , except that, in that study, the lactation‐induced changes in kisspeptin expression were restricted to the ARC population. Similarly, a number of other rat studies have reported lactation‐induced changes in kisspeptin expression in the ARC, with much less pronounced effects seen in the RP3V . Taken together with the present work and our previous study that showed a specific loss of RP3V kisspeptin inputs to GnRH neurones during lactation , these studies suggest that there may be a species difference between rats and mice, in that the different populations of kisspeptin neurones might be relatively more important for the suppression of fertility during lactation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present data showing only partial reversal of the lactation‐induced suppression of kisspeptin expression in the RP3V of mice by bromocriptine are strikingly similar to that recently reported in rats , except that, in that study, the lactation‐induced changes in kisspeptin expression were restricted to the ARC population. Similarly, a number of other rat studies have reported lactation‐induced changes in kisspeptin expression in the ARC, with much less pronounced effects seen in the RP3V . Taken together with the present work and our previous study that showed a specific loss of RP3V kisspeptin inputs to GnRH neurones during lactation , these studies suggest that there may be a species difference between rats and mice, in that the different populations of kisspeptin neurones might be relatively more important for the suppression of fertility during lactation.…”
Section: Discussionsupporting
confidence: 86%
“…Prolactin receptors are expressed in the majority of kisspeptin neurones in both populations , and prolactin has recently been shown to induce the phosphorylation of signal transducer and activator of transcription 5 (pSTAT5) in ARC kisspeptin neurones in the rat . Moreover, during lactation, when prolactin levels are elevated, there is a marked loss of Kiss1 mRNA and kisspeptin protein in the ARC of the rat . Chronic infusion of prolactin in female mice abolished oestrous cyclicity and suppressed global Gnrh and Kiss1 mRNA expression in the hypothalamus, whereas kisspeptin therapy restored oestrous cycles in hyperprolactinaemic mice , consistent with the hypothesis that prolactin‐induced suppression of GnRH secretion is mediated by an inhibition of kisspeptin neurones.…”
mentioning
confidence: 99%
“…2011 , Araujo-Lopes et al . 2014 , Ladyman & Woodside 2014 ), and in both populations in the mouse ( Brown et al . 2014 ).…”
Section: Neuroendocrine Functions Of Prolactinmentioning
confidence: 99%
“…58 The pathways linking the suckling stimulus to the suppression of ovulation, however, are unclear. Kiss1 mRNA and protein levels are reduced in the arcuate nucleus of lactating rats associated with the suppression of pulsatile GnRH secretion during lactation, 42,[59][60][61][62][63] and in both populations of kisspeptin neurons in the mouse. 48 The RP3V kisspeptin population is apparently harder to study in rats 59,64 providing conflicting findings, such as reports of Kiss1 mRNA remaining unchanged during lactation, 59 kisspeptin protein increasing while Kiss1 mRNA labeling decreased during lactation, 60 or even suckling-induced decrease of Kiss1 mRNA.…”
Section: Role Of Prolactin In Lactational Infertilitymentioning
confidence: 98%